NIRS monitoring of quality parameters and digestibility of new lucerne cultivars in Northern Italy - Odoardi M.; Tomasoni C.; Borrelli L.; Pintus B.; Ursino A. (Quality in lucerne and medics for animal production, 2001)
Adaptation of the new lucerne cultivars to different environmental conditions in Northern Italy is routinely tested in replicated field trials organised by the Experimental Institute of Forage Crops. The continuous monitoring of the new accessions of the National Register of Varieties allows the organisation of Recommended Lists useful to farmers and extension officers. In addition to the traditional bio-agronomic traits, routinely controlled for inscription to the Register, the chemical composition of dry matter and the organic matter digestibility are now being determined and acquired for all the cultivars under evaluation. The second cycle, late-spring harvest, is used for near infrared reflectance spectroscopy analysis, using calibration equations previously prepared and checked for validation with a set of wet analyses. Results of the nutritional evaluation of the new lucerne varieties in the National List are reported and discussed for their best utilisation.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)